2017
DOI: 10.1002/ejic.201700235
|View full text |Cite
|
Sign up to set email alerts
|

Pt and Ti Complexes Immobilized onto Mesoporous Silica Microspheres and Their Interaction with Molecules of Biological Interest

Abstract: Mesoporous silica microspheres (MSMs) have been functionalized with triazole and pendant hydroxy moieties by a postsynthetic procedure. The functionalities have been prepared by a very efficient azide/alkyne click reaction with propargyl alcohol to yield the corresponding 1,2,3‐triazole. The subsequent reaction with cisplatin and titanocene as metallic precursors produces platinum and titanium complexes tethered onto the silica surface. The synthesized materials have been fully characterized by dynamic recryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
(77 reference statements)
1
9
0
Order By: Relevance
“…367 Other drug release experiments were performed on mesoporous silica microspheres functionalized by metal (Pt and Ti) complexes, studying the interaction and the release dynamics of guanosine and bovine serum albumin by means of FT-IR and 13 C MAS-NMR: DFT calculations supported the experiments by modelling the interaction energies and the adsorption/desorption mechanisms. 368 MCM-41 and SBA-15 were tested as potentials carriers for a poorly soluble drug (Nimodipine), which was shown to be incorporated either in crystalline or in amorphous form, the latter being markedly more resistant to washing: the properties of the loaded samples were characterized by several techniques, including FT-IR and DFT calculations, which were used to interpret the vibrational spectra (modelling the bulk Nimodipine molecule). 369…”
Section: Mesoporous Solids For Drug Deliverymentioning
confidence: 99%
“…367 Other drug release experiments were performed on mesoporous silica microspheres functionalized by metal (Pt and Ti) complexes, studying the interaction and the release dynamics of guanosine and bovine serum albumin by means of FT-IR and 13 C MAS-NMR: DFT calculations supported the experiments by modelling the interaction energies and the adsorption/desorption mechanisms. 368 MCM-41 and SBA-15 were tested as potentials carriers for a poorly soluble drug (Nimodipine), which was shown to be incorporated either in crystalline or in amorphous form, the latter being markedly more resistant to washing: the properties of the loaded samples were characterized by several techniques, including FT-IR and DFT calculations, which were used to interpret the vibrational spectra (modelling the bulk Nimodipine molecule). 369…”
Section: Mesoporous Solids For Drug Deliverymentioning
confidence: 99%
“…However, mesoporous silica-based materials have also been functionalized with metallodrugs of interest in cancer treatment, such as platinum compounds [7,8,9,10,11,12,13,14], titanium compounds [10,15,16,17,18,19,20,21,22,23], tin compounds [22,24,25] and even ruthenium photosensitizers [26], observing promising anticancer activity and a potential future application in clinical trials. The cellular action of these metallodrug-functionalized nanostructured silica-based materials showed that, in most cases, the nanosystems do not release the metallodrug to the biological medium (or the metallodrug release rates are very low), and they usually act as “non-classical” drug-delivery systems, whose cytotoxic activity is due to the action of the entire nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have validated the effectiveness of this method in confirming the inclusion of various ligands or metal complexes within nanostructured silica. 24,25 As depicted in Figure 1, the DR UV-Vis spectra of the materials revealed a discernible signal around 200-207 nm, indicative of the presence of AP ligands. This observation aligns with findings from similar materials incorporating analogous ligands, reaffirming successful integration within the structure.…”
Section: Uv-visible Measurementsmentioning
confidence: 97%